Aging Injury Impairs Structural Properties and Cell Signaling in Human Red Blood Cells; Açaì Berry Is a Keystone - Sara Spinelli; Elisabetta Straface; Lucrezia Gambardella; Daniele Caruso; Giuseppe Falliti; Alessia Remigante; Angela Marino; Rossana Morabito (MDPI AG, 2023)
Red blood cell (RBC) deformability is the ability of cells to modulate their shape to ensure transit through narrow capillaries of the microcirculation. A loss of deformability can occur in several pathological conditions, during natural RBC aging through an increase in membrane protein phosphorylation, and/or through the structural rearrangements of cytoskeletal proteins due to oxidative conditions, with a key role played by band 3. Due to the close relationship between aging and oxidative stress, flavonoid-rich foods are good candidates to counteract age-related alterations. This study aims to verify the beneficial role of Açaì extract in a d-Galactose (d-Gal)-induced model of aging in human RBCs. To this end, band 3 phosphorylation and structural rearrangements in membrane cytoskeleton-associated proteins, namely spectrin, ankyrin, and/or protein 4.1, are analyzed in RBCs treated with 100 mM d-Gal for 24 h, with or without pre-incubation with 10 μg/mL Açaì extract for 1 h. Furthermore, RBC deformability is also measured. Tyrosine phosphorylation of band 3, membrane cytoskeleton-associated proteins, and RBC deformability (elongation index) are analyzed using western blotting analysis, FACScan flow cytometry, and ektacytometry, respectively. The present data show that: (i) Açaì berry extract restores the increase in band 3 tyrosine phosphorylation and Syk kinase levels after exposure to 100 mM d-Gal treatment; and (ii) Açaì berry extract partially restores alterations in the distribution of spectrin, ankyrin, and protein 4.1. Interestingly, the significant decrease in membrane RBC deformability associated with d-Gal treatment is alleviated by pre-treatment with Açaì extract. These findings further contribute to clarify mechanisms of natural aging in human RBCs, and propose flavonoid substances as potential natural antioxidants for the treatment and/or prevention of oxidative-stress-related disease risk.